The Effect Of Contextual Learning In Civic Education On Students' Character Development - Komalasari, Kokom (Penerbit Universiti Sains Malaysia, 2012)
The long, multidimensional crises in Indonesia have been rooted in degraded national morality. To improve this national moral quality, the country has needed a revitalisation of civic education's role in "value-based education" and "nation and character building". Therefore, civic education has developed to include contextual learning, which is assumed to improve students' character. The problem studied here was the following: What is the effect of contextual learning in civic education on students' character development? This study used quantitative and qualitative approaches with "a dominant-less dominant design". The quantitative approach used surveys, and the qualitative approach used interviews to gather data. The population of interest was junior high school students in West Java taught by civic education teachers who had followed Competence-based Integrated Training. The research sample was determined based on cluster sampling, proportional, and systematic random sampling techniques, with a final sample of 1004 junior high school students. This study's findings showed that contextual learning in civic education had a strong positive relationship with the character development of the junior high school students. This research finding explained that first, contextual learning in civic education taught student's life skills, including the principles of interdependence, differentiation, and self-regulation; second, contextual learning in civic education encouraged the establishment of democratic learning; third, contextual learning in civic education includes elements of character development; and fourth, character education in civic education helped students discover and develop local moral values.